Manifestations of pain sensitization across different painful knee disorders: A systematic review including meta-analysis and metaregression - De Oliveira Silva, Danilo; Rathleff, Michael Skovdal; Petersen, Kristian; De Azevedo, Fabio Mıcolis [UNESP]; Barton, Christian John (Oxford University Press (OUP), 2019)
Objectives. Previous reviews have reported that manifestations of pain sensitization may play an important role in the pain experienced by people with knee osteoarthritis. However, it is unknown if manifestations of pain sensitization are common features across other painful knee disorders or if sensitization requires targeted intervention. This review aims to synthesize the published research investigating manifestations of pain sensitization in painful knee disorders and to evaluate if the manifestations of pain sensitization change in response to treatment. Methods. The systematic review protocol was registered with PROSPERO (CRD42015024211). We searched Medline, Embase, CINAHL, Web of Science, Sportsdiscus, and Cochrane Central for studies that investigated between-group differences (knee pain vs pain-free subjects) or the effect of treatment on manifestations of pain sensitization. Two reviewers independently assessed studies for inclusion and quality. Available data were synthesized via predetermined levels of evidence, meta-analysis, and metaregression where possible. Results. Fifty-two studies investigating evidence related to pain sensitization distributed across four different painful knee disorders were identified. Conclusions. Our meta-analysis provides evidence of pain sensitization in people with knee osteoarthritis (strong evidence), people with patellofemoral pain (moderate evidence), and postmeniscectomy patients (very limited evidence). However, conflicting evidence exists in patellar tendinopathy. Metaregression indicates that pain is associated with pressure pain thresholds in knee osteoarthritis. In people with knee osteoarthritis and patellofemoral pain, several interventions were found to reduce manifestations of pain sensitization. This review highlights that pain sensitization may be amenable to treatment through exercise therapy, mobilization, and pharmacological and surgical intervention.
Keywords: Hyperalgesia; Knee Pain; Osteoarthritis; Quantitative Sensory Testing